2016
DOI: 10.1016/j.visres.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of visual performance by d -serine in models of inner and outer retinal dysfunction assessed using sweep VEP measurements in the conscious rat and rabbit

Abstract: The NMDA subtype of glutamate receptor and its co-agonist d-serine play a key role in synaptic function in the central nervous system (CNS), including visual cortex and retina. In retinal diseases such as glaucoma and macular degeneration, a loss of vision arises from malfunction of retinal cells, resulting in a glutamate hypofunctional state along the visual pathway in the affected parts of the visual field. An effective strategy to remedy this loss of function might be to increase extracellular levels of d-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 53 publications
0
7
0
1
Order By: Relevance
“…We have previously reported that rats exposed to blue light have long-lasting and stable deficits in contrast sensitivity that can be acutely improved by systemic administration of D-serine (Staubli et al, 2016). In the current experiments, a group of rats was used 53 weeks after blue light exposure that had a stable contrast sensitivity deficit of approximately 6 (Fig.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…We have previously reported that rats exposed to blue light have long-lasting and stable deficits in contrast sensitivity that can be acutely improved by systemic administration of D-serine (Staubli et al, 2016). In the current experiments, a group of rats was used 53 weeks after blue light exposure that had a stable contrast sensitivity deficit of approximately 6 (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Effects of PG Analogs in Models of Visual Function. Since we have previously shown that systemically applied D-serine can have beneficial effects on visual function (Staubli et al, 2016), L-4FPG and L-4OHPG were tested in naive rats for their ability to influence normal vision (Fig. 6).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations